Partitioning of injuries caused by winter, fungal diseases and viral infections in cereals - Peltonen, Jari (Agricultural Research Centre of Finland, 1993)
Tutkimuksessa määritettiin rukiin talvituhojen, kevätvehnän härmäsaastunnan ja kauran BYDV:N (ohran kääpiökasvuviruksen) raja-arvoja sadonmuodostuksen kannalta. Talvituhot rajoittivat rukiin sadonmuodostusta voimakkaasti, mikäli kylvetystä pinta-alasta oli tuhoutunut yli 19 %. Jos Septoriasaastunta oli voimakkaampi kuin 37 %, heikensi infektio satotasoa selvästi. BYDV:N aiheuttama satotappio oli merkittävä mikäli enemmän kuin 38 % lehdistöstä oli saastunut. Kyseisten sadonmuodostusta rajoittavien stressien aiheuttama sadon menetys oli mallin mukaan rukiilla keskimäärin 44 % (1804 kg/ha), kevätvehnällä 33 % (1393 kg/ha) ja kauralla 30 % (1718 kg/ha). Tutkimuksessa on pohdittu stressiraja-arvojen merkitystä arvioitaessa viljojen vuosittaisia satovaihteluita.

The objective of this study was to clarify whether the critical levels of winter damage, viral infections and foliar diseases of cereals could be established by the Cate-Nelson procedure. This information would help the State Granary representatives and computer modelists, as well as farmers and consultants to understand the yearly variations in grain yields of cereals. Three winter rye, spring wheat and oat cultivars were used. The severity of leaf diseases and percentages of winter damage were observed visually. When winter damage exceeds 19%, a yield reduction of 44% (1804 kg ha-1) in winter rye may be expected. The critical level of Septoria nodorum infection in spring wheat was 37%. Above this critical level a yield reduction of 33% (1393 kg ha-1) was estimated. In oat canopy an area of > 38% infected by barley yellow dwarf virus (BYDV) decreased the grain yield significantly by 30% (1718 kg ha-1).
Keywords: Ka; Ta; viljat; ruis; Secale cereale; kaura; Avena sativa; sadonmuodostus; talvivauriot; winter rye; spring wheat; oats; winter damage; foliar diseases